Operative, long‐term and quality of life outcomes after salvage of failed re‐do ileal pouch anal anastomosis. (23rd February 2022) - Esen, Eren; Lynn, Patricio B.; Da luz Moreira, Andre; Erkan, Arman; Aytac, Erman; Grieco, Michael J.; Kirat, Hasan T.; Remzi, Feza H.
Abstract: Aim: Approximately 20%–40% of the patients with re‐do ileal pouch anal anastomosis (IPAA) experience pouch failure. Salvage surgery can be attempted in this patient group with severe aversion to permanent ileostomy. The literature regarding secondary IPAA revision after re‐do IPAA failure is scarce. Methods: All patients who underwent a secondary IPAA revision after re‐do IPAA failure between September 2016 and July 2021 in a single centre were included. Short‐ and long‐term outcomes and quality of life in this patient group are reported. Results: Ten patients who had secondary IPAA revision for re‐do IPAA failure were included. All patients had ulcerative colitis. Nine of these patients had pelvic sepsis and one patient had a mechanical issue. Mucosectomy and handsewn anastomosis was performed in nine patients. The existing pouch was salvaged in six patients and four patients had pouch excision and re‐creation. Two patients had postoperative pelvic sepsis. Pouch retention rate was 78% in a median of 28 months. None of the patients had short‐gut syndrome. The procedure was associated with good quality of life (median Cleveland Global Quality of Life Index 0.8). All patients would undergo the same surgery if needed. Conclusion: Secondary IPAA revision after a failed re‐do IPAA can be an option in patients with severe aversion to permanent ileostomy if re‐do IPAA fails and it is associated with good outcomes. This patient group should be carefully evaluated and referred to specialized centres if required.